Microbial flocculant produced by a novel Paenibacillus sp., strain A9, using food processing wastewater to replace fermentation medium and its application for the removal of Pb(II) from aqueous solution. Issue 9 (December 2019) - Jiang, Binhui; Fu, Lili; Cao, Wan; Zhang, Bo; Li, Fengda; Liu, Yana
Due to high production costs, the popularization and application of microbial flocculants in the field of water treatment have been limited. In this study, the capture of lead ions by the fermentation broth of a novel Paenibacillus sp. strain A9 and cultured with food wastewater was further investigated. The results revealed that the production of MBFA9 could be increased significantly by adding a small amount of carbon and nitrogen to food wastewater. Under the best experimental conditions (pH 8.5, culture temperature 30°C, 150 r/min), adding 1% (m/v) carbon and 0.1% (m/v) nitrogen to 1% (v/v) wastewater resulted in a yield of MBFA9 of 6.29 g/l. At a temperature of 30°C, pH of 5, contact time of 35 min, and FBA9 dosage of 5%, the removal rate and removal capacity of Pb(II) reached the highest values of 95.1% and 317 mg/g, respectively. Field emission scanning electron microscopy analysis indicated that bacterial cells, metabolite small molecule acids, and MBFA9 in FBA9 all contributed to the removal of Pb(II). Fourier-transform infrared spectrometry analysis indicated that functional groups such as –OH, –COOH, –CO, and –NH2 existed in MBFA9 and on the cell surface. Various mechanisms involved in Pb(II) removal can occur simultaneously, including cell surface adsorption, microcrystallization, and biological flocculation.